The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jcom.12327
|View full text |Cite
|
Sign up to set email alerts
|

Still an Agenda Setter: Traditional News Media and Public Opinion During the Transition From Low to High Choice Media Environments

Abstract: This study analyzes whether the agenda-setting influence of traditional news media has become weaker over time-a key argument in the "new era of minimal effects" controversy. Based on media content and public opinion data collected in Sweden over a period of 23 years , we analyze both aggregate and individual-level agenda-setting effects on public opinion concerning 12 different political issues. Taken together, we find very little evidence that the traditional news media has become less influential as agenda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 41 publications
2
43
0
3
Order By: Relevance
“…Media scholars, therefore, have called for research that tests assumptions, and that describes the role, if any, of newspapers in democratic politics (Bennett and Pfetsch 2018;Pfetsch 2018). These scholars now often focus on "disrupted public spheres" (Bennett and Pfetsch 2018, 245) or what has been described as changing or pluralizing media landscapes or environments (see e.g., Bennett and Iyengar 2008;Djerf-Pierre and Shehata 2017;Bennett and Livingston 2018;Blumler 2018). Authors suggest that we are seeing an emergent disinformation order, characterized by divided, disrupted, dissonant and disconnected public spheres, developments which challenge assumptions about coherent, functional, systemic democratic public spheres (Bennett and Livingston 2018;Bennett and Pfetsch 2018;Pfetsch 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Media scholars, therefore, have called for research that tests assumptions, and that describes the role, if any, of newspapers in democratic politics (Bennett and Pfetsch 2018;Pfetsch 2018). These scholars now often focus on "disrupted public spheres" (Bennett and Pfetsch 2018, 245) or what has been described as changing or pluralizing media landscapes or environments (see e.g., Bennett and Iyengar 2008;Djerf-Pierre and Shehata 2017;Bennett and Livingston 2018;Blumler 2018). Authors suggest that we are seeing an emergent disinformation order, characterized by divided, disrupted, dissonant and disconnected public spheres, developments which challenge assumptions about coherent, functional, systemic democratic public spheres (Bennett and Livingston 2018;Bennett and Pfetsch 2018;Pfetsch 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, any of the advantages of social media that have been heralded over the last decades ought to be reviewed critically. Pessimistic voices stress the maintenance of inequalities (e.g., unequal access to media) and the news media’s interdependency to traditional media and institutions, possibly reinforcing existing dominant modes of discourse (Djerf-Pierre and Shehata 2017; Gerhards and Schäfer 2010; Goode 2009). In addition, keeping in mind a more skeptic or ironic audience (Chouliaraki 2013), it is equally possible that the audience is not even interested in engaging and communicating with far-away media users, including distant victims.…”
Section: Media Users In a Changing Media Landscapementioning
confidence: 99%
“…Social media have been seen to be increasingly used by Internet users to stay informed, share news, and to actively participate in the production of news content (Feezell 2018; Purcell et al 2010). However, other scholars have demonstrated that television is still the main source for news information (Costera Meijer and Groot Kormelink 2015; Vanhaelewyn and Lieven 2016 3 ; Djerf-Pierre and Shehata 2017) even if this source is increasingly complemented by online resources (Nielsen and Schrøder 2014; Picone et al 2015). People are thus “checking, sharing, clicking and linking” their way through the news (Costera Meijer and Groot Kormelink 2015, 664), but there is little evidence so far that people are indeed fully making use of the interactive potential.…”
Section: Media Users In a Changing Media Landscapementioning
confidence: 99%
“…Another explanation for not finding distinct media effects for the use of traditional media types might be that the study was done in a country where there is a high level of agreement of journalistic news values and practices among journalists (Djerf-Pierre & Shehata, 2017). Thus, the content variations in how different media types report on immigration might not be large enough to generate distinct effects.…”
Section: Discussionmentioning
confidence: 96%